Complement activation turnover on surfaces of nanoparticles. (August 2017) - Moghimi, S.M.; Simberg, D.
Graphical abstract: Highlights: Adsorbed proteins play a role in complement activation at nanoparticle surface. The complement protein C3b can attack adsorbed proteins. Protein-C3b complexes are continuously formed and released. New design approaches are suggested for overcoming complement activation. Abstract: The complement system is an important component of the innate immune system, which contributes to non-specific host defence. Particulate matters, such as invading pathogens and nanomedicines, in the blood may activate the complement system through classical, lectin and alternative pathways. Complement activation can aid recognition and clearance of particulate matters by immune cells, but uncontrolled complement activation can inflict damage and be life threatening. Plasma proteins on adsorption to surfaces of nanoparticles also play a significant role in complement activation and particularly through the alternative pathway. This process is continuous and changeable in vivo; protein-complement complexes are formed on the nanoparticle surface and then released and the cycle repeats on further plasma protein deposition. This complement activation turnover poses a challenge for design of immune-safe nanomedicines.